1987
DOI: 10.1203/00006450-198709000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Piglet Small Intestine after Cholesterol Deprivation

Abstract: ABSTRACT. Mammalian cells require cholesterol for normal cell function. This requirement can be fulfilled by endogenous biosynthesis or by extracellular supplementation. Infants fed with human milk receive greater quantities of cholesterol than those fed commercial formulas. Whether this lack of cholesterol in commercial formulas poses a threat to normal neonatal cell function is not known. We compared small intestinal microvillus membrane fluidity, hydrolase activities, protein concentration, permeability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…Moreover, liver apoE mRNA rises in 10-hour-fasted suckling rats as compared with controls, suggesting that the apoE gene expression in the rat liver cells changes during development in relation to insulin and glucagon levels [11]. The importance of cholesterol and phospholipid contents to the integrity of the small intestine microvillus membrane during the weaning transitional changes [42,43], which might be influenced by apoE, has been suggested. Furthermore, increased apolipoprotein gene expression accompanies the differentiation in intestinal cell lines in vitro [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liver apoE mRNA rises in 10-hour-fasted suckling rats as compared with controls, suggesting that the apoE gene expression in the rat liver cells changes during development in relation to insulin and glucagon levels [11]. The importance of cholesterol and phospholipid contents to the integrity of the small intestine microvillus membrane during the weaning transitional changes [42,43], which might be influenced by apoE, has been suggested. Furthermore, increased apolipoprotein gene expression accompanies the differentiation in intestinal cell lines in vitro [44].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat has been shown to influence both the morphology and the function of the intestinal epithelium. Several investigators have found that the type and amount of lipid in formulas and milk significantly affect the transport properties and permeability of the neonatal intestinal epithelium and the rate at which it proliferates and matures (46,54,61). In a neonatal pig model of NEC, Crissinger and co-workers (12,56,57) showed that the degree of permeability and intestinal damage directly relates to the presence and type of fat in various neonatal formulas.…”
mentioning
confidence: 99%
“…Noting that aminopeptidase A mRNA abundance was lower in the CON than in the DLM and HMTBA groups, we proposed that increased maternal consumption of methionine might promote degradation and subsequent absorption of milk protein by neonatal pigs. Oxysterol binding protein-related protein 10 has been implicated in sterol containing cholesterol transport [ 42 , 43 ], and low level of cholesterol is considered good for small intestinal microvillus membrane fluidity [ 44 ]. In this regard, decreased expression of oxysterol binding protein-related protein 10 following increased maternal consumption of methionine as DLM and HMTBA might suggest the facilitation of nutrients transport in the small intestine.…”
Section: Discussionmentioning
confidence: 99%